Melanoma Affects the Composition of Blood Cell-Derived Extracellular Vesicles - Koliha, Nina; Heider, Ute; Ozimkowski, Tobias; Wiemann, Martin; Bosio, Andreas; Wild, Stefan (Frontiers in Immunology, 2016)
Extracellular vesicles are specifically loaded with nucleic acids, lipids, and proteins from their parental cell. Therefore, the constitution of extracellular vesicles reflects the type and status of the originating cell and extracellular vesicles in melanoma patient’s plasma could be indicative for the tumor. Likewise, extracellular vesicles might influence tumor progression by regulating immune responses. We performed a broad protein characterization of extracellular vesicles from plasma of melanoma patients and healthy donors as well as from T cells, B cells, natural killer cells, monocytes, monocyte-derived dendritic cells and platelets using a multiplex bead-based platform. Using this method, we succeeded in analyzing 58 proteins that were differentially displayed on extracellular vesicles. Hierarchal clustering of protein intensity patterns grouped extracellular vesicles according to their originating cell type. The analysis of extracellular vesicles from stimulated B cells and monocyte-derived dendritic cells revealed the transfer of surface proteins to vesicles depending on the cell status. The protein profiles of plasma vesicles resembled the protein profiles of extracellular vesicles from platelets, antigen presenting cells and natural cells as shown by platelet markers, costimulatory proteins, and a natural killer cell subpopulation marker. In comparison to healthy plasma vesicles, melanoma plasma vesicles showed altered signals for platelet markers indicating a changed vesicle secretion or protein loading of extracellular vesicles by platelets and a lower CD8 signal that might be associated with a diminished activity of natural killer cells or T cells. As we hardly detected melanoma-derived vesicles in patient’s plasma, we concluded that blood cells induced the observed differences. In summary, our results question a direct effect of melanoma cells on the composition of extracellular vesicles in melanoma plasma, but rather argue for an indirect influence of melanoma cells on the vesicle secretion or protein loading by blood cells.